FORMAÇÃO CONTINUADA DE PROFESSORES ALFABETIZADORES: ANÁLISE DO PACTO NACIONAL PELA ALFABETIZAÇÃO NA IDADE CERTA - Cruz, Mirian Margarete Pereira da (2016)
This paper presents an analysis of the National Pact for Literacy in the Age One - PNAIC,which has been effected by the Ministry of Education, in the Brazilian states and the Federal District, since 2013. It is a continuing education program for school teachers of the Cycle Literacy. The proposed program was developed and designed in the government's management Dilma Vana Rousseff (2011/2014), in order to contribute to the process of teaching and student learning in the early years, in the area of literacy / language arts and mathematics. However, the implementation of this program coming up in structural difficulties related to the teacher's pedagogic practice, ranging from the design they have about literacy to the actual conditions for the learning process of students. So, if delineated as a central problem for the development of this research the following question: how was effective deployment and implementation of the National Pact for Literacy in the Age One (PNAIC) from the programs for continuing education teachers previously developed? For the development of the research was defined as general objective: to analyze the deployment and implementation of the National Pact for Literacy in Certain Age, from programs for continuing education of teachers that preceded it. To reach this goal, it was defined as specific objectives: to understand the historical context and its determinants,which engendered the continuing education programs for teachers in the early years of elementary school; understand the design and implementation of educational policies for continuing training of literacy teachers; pointing out the limits and advances of PNAIC. The research was carried out by means of literature, using as theoretical framework authors dealing with issues of continuing education, literacy and Historical-Critical Pedagogy. From the literature, the analysis of primary and secondary sources, related to the theme of the study allowed us to analyze the intentions and the multiple determinants that engender the continuing education of teachers. The theoretical and methodological axis is expressed by the historical and dialectical materialism, in that it enables the analysis of the total, showing the contradictions in capitalist society. The results showed the limits and advances in literacy teacher training policy, proposed by the National Pact for Literacy in the Age One.The development of policies for the training of teachers is an essential step for us to change the educational landscape and contribute to a truly emancipatory education and to ensure learning and our students. Through this program, changes were perceived in the pedagogical practice of teachers. However, it is essential to point out that programs do not change educational deficits overnight, because joints are needed with other political actions, which do not depend on the continuing education of teachers.